2014
DOI: 10.1186/1471-2407-14-97
|View full text |Cite
|
Sign up to set email alerts
|

Up-regulated MicroRNA-181a induces carcinogenesis in Hepatitis B virus-related hepatocellular carcinoma by targeting E2F5

Abstract: BackgroundAccumulating evidence showed that microRNAs are involved in development and progression of multiple tumors. Recent studies have found that miR-181a were dysregulated in several types of cancers, however, the function of miR-181a in hepatocellular carcinoma (HCC) remains unclear. In this study we assessed the potential association between miR-181a, HBV and HCC.MethodsThe expression of miR-181a in HBV-expressing cells was determined by using qRT-PCR. Dual-Luciferase reporter Assay, qRT-PCR and western … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
42
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(43 citation statements)
references
References 19 publications
1
42
0
Order By: Relevance
“…MiR-122, a special miRNA of liver had been found to downregulate after HBV infection in several studies [13]. In addition, miRNA, including miR-1 [14], miR-181a [15], miR-372 [16], miR-501 [17], was reported to upregulate after HBV infection. Moreover, some miRNAs have been identified to vary according to the development level of disease.…”
Section: Discussionmentioning
confidence: 97%
“…MiR-122, a special miRNA of liver had been found to downregulate after HBV infection in several studies [13]. In addition, miRNA, including miR-1 [14], miR-181a [15], miR-372 [16], miR-501 [17], was reported to upregulate after HBV infection. Moreover, some miRNAs have been identified to vary according to the development level of disease.…”
Section: Discussionmentioning
confidence: 97%
“…The cell migration and invasion were assayed using Transwell ® chambers (8 µm; Corning Costar, Cambridge, MA, USA). For the Transwell ® migration assay, 1x10 5 transfected cells (miR 133a mimics and NC) were placed into the upper chamber, which was cultured in medium with 2% FBS, while 500 µl RPMI-1640 medium containing 20% FBS was added to the lower chamber. For the Transwell ® invasion assay, a Transwell ® chamber coated with Matrigel ® (BD Biosciences, San Jose, CA, USA) and a total of 1x10 5 cells were seeded into the upper chamber, while the lower chamber was incubated with 500 µl RPMI-1640 medium containing 20% FBS.…”
Section: -(4 5-dimethylthiazol-2-yl)-25-diphenyltetrazolium Bromidmentioning
confidence: 99%
“…HCC accounts for between 85 and 90% of all cases of primary liver cancer and is the third leading cause of mortality from cancer worldwide and the fifth most common type of malignancy (1)(2)(3)(4). It has been reported that ~21,000 cases of HCC are diagnosed and ~700,000 patients succumb to the disease worldwide annually (5). The established risk factors of HCC include viral hepatitis, alcohol abuse and non-alcoholic fatty liver disease (6).…”
Section: Introductionmentioning
confidence: 99%
“…As in glioblastoma, significant downregulation of hsa-miR-181a was also observed in squamous lung cell carcinoma,83 oral squamous cell carcinoma,71 luminal A-like breast cancer,67 and non-small-cell lung cancer 84. However, hsa-miR-181a was significantly overexpressed in MCF-7 breast cancer cells,85 colorectal cancer,28 and hepatocellular carcinoma cells 56,86,87. Hsa-miR-181a was upregulated in acute myeloid leukemia,76 especially in the M1 and M2 subtypes, and in myelodysplastic syndromes88 but downregulated in multiple myeloma89 and chronic lymphocyte leukemia 79,90.…”
Section: Discussionmentioning
confidence: 96%